Analisis efektivitas penggunaan media pembelajaran papan “FAKOPI” terhadap hasil belajar siswa kelas IV MI NU Hidayatul Mubtadiin - Nurullaika, Nurullaika (Maliki Interdisciplinary Journal, 2024)
The rapid development of technology does not have to force us to abandon the old methods in the learning process. The old methods are still used because of the conditions of the school where we teach. As mentioned earlier, the learning process consists of several important components, one of which is learning media. Media is one of the most important learning resources in the learning process. In this study, based on school conditions, teachers still use conventional media in the learning process. One of them is the “Fakopi” board media, which is used in Indonesian language learning in class IV MI NU Hidayatul Mubtadiin. The purpose of this study was to determine how effective the use of this media is on the learning outcomes of grade IV students of MI NU Hidayatul Mubtadiin. The results of this study indicate that the use of “Fakopi” board learning media is very effective on the learning outcomes of grade IV students of MI NU Hidayatul Mubtadiin. It is hoped this research can inspire teachers to realize that creating interesting learning is not only limited to the digital world, but simple media is still effective in the learning process.